Chromosomal-level genome and multi-omics dataset of Pueraria lobata var. thomsonii provide new insights into legume family and the isoflavone and puerarin biosynthesis pathways. Issue 1 (19th January 2022) - Shang, Xiaohong; Yi, Xinxin; Xiao, Liang; Zhang, Yansheng; Huang, Ding; Xia, Zhengbao; Ou, Kunpeng; Ming, Ruhong; Zeng, Wendan; Wu, Dongqing; Cao, Sheng; Lu, Liuyin; et al.
Abstract: Pueraria lobata var. thomsonii (hereinafter abbreviated as Podalirius thomsonii ), a member of legumes, is one of the important traditional Chinese herbal medicines, and its puerarin extraction is widely used in health and pharmaceutical industry. Here, we assembled a high-quality genome of P. thomsonii using long-read single-molecule sequencing and Hi-C technologies. The genome assembly is approximately 1.37 Gb in size and consists of 5145 contigs with a contig N50 of 593.70 Kb, further clustered into 11 pseudochromosomes. The genome structural annotation resulted in about 869.33 Mb (about 62.70% of the genome) repeat regions and 45 270 protein-coding genes. Genome evolution analysis revealed that P. thomsonii is most closely related to soybean and underwent two ancient whole-genome duplication events, one was in the common ancestor shared by legume species, the other occurred independently at around 7.2 million years ago after its specification. A total of 2373 gene families were found unique in P. thomsonii comparing to five other legume species. Genes and metabolites related to puerarin content in tuberous tissues were characterized. A total of 572 genes upregulated in the puerarin biosynthesis pathway were identified, and 235 candidate genes were further enriched by omics data. Furthermore, we identified 6 8-C-glucosyltransferase (8-C-GT) candidate genes significantly involved in puerarin metabolism. Our study filled in a key genomic gap in legume family, and provided valuable multi-omic resources for the genetic improvement of P. thomsonii .